2023
DOI: 10.7759/cureus.34531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anxiety Associated With MRI Examination Among the General Population in the Western Region of Saudi Arabia

Abstract: BackgroundWhile magnetic resonance imaging (MRI) is one of the most efficient diagnostic methods used today, some patients may find an MRI examination to be a frightening experience. The proximity to the machine during screening and being in a confined space can cause a feeling of claustrophobia. Severe anxiety during MRI screening can cause the patient to move, which lowers the quality of the imaging and diagnostic test, and can result in the early termination of the MRI examination and the patient declining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…There is limited research on the incidence and prevalence of HZ in Saudi Arabia. In one study conducted in Saudi Arabia, the reported seroprevalence of varicella was about 86% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research on the incidence and prevalence of HZ in Saudi Arabia. In one study conducted in Saudi Arabia, the reported seroprevalence of varicella was about 86% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the noise generated by the equipment is large, and pregnant women lack the perception and control of the external environment, and tend to feel fear or anxiety [ 11 ]. On the other hand, women are more anxious than men in magnetic resonance examinations [ 12 ]. Due to different physiological mechanisms, physical fitness and social environments, women are more likely to show emotional behavior [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, confined space, loud noises, and the requirement for patients to remain still during the procedure can induce anxiety and discomfort, leading to suboptimal image quality and compromised patient experience. Sedation is commonly employed to alleviate patient apprehension and facilitate cooperation during MRI scans [2]. Effective sedation enhances patient comfort and cooperation during MRI examinations [3].…”
Section: Introductionmentioning
confidence: 99%